Cover Picture: Efficient and Scalable Production of 2D Material Dispersions using Hexahydroxytriphenylene as a Versatile Exfoliant and Dispersant (ChemPhysChem 11/2016). Issue 11 (23rd May 2016) - Liu, Gang; Komatsu, Naoki
Abstract : The Front Cover picture shows how 2D materials are exfoliated in the presence of hexahydroxytriphenylene by sonication in solution phase and by ball milling in solid phase. More information can be found in the Full Paper by G. Liu and N. Komatsu onpage 1557 in Issue 11, 2016 (DOI:10.1002/cphc.201600187 .